Projected increases in potential groundwater recharge and reduced evapotranspiration under future climate conditions in West Africa - P.A. Cook; E.C.L. Black; A. Verhoef; D.M.J. Macdonald; J.P.R. Sorensen (Journal of Hydrology: Regional Studies, 2022)
Study region: West Africa, with a focus between 5°W and 5°E. Study focus: The effects of changing climate and CO2 concentration (RCP8.5 between 2000 and 2100) on the West African monsoon are examined using the UPSCALE high-resolution (25 km) global climate model ensembles for present and future climate, combined with the JULES land-surface model. New hydrological insights: Future climate is predicted to have an enhanced summertime Saharan heat low, changing large-scale circulation, causing monsoon rainfall generally to increase. The monsoon progresses further inland and occurs later in the year. UPSCALE rainfall projections indicate that the eastern Sahel becomes wetter (+ 12.2%) but the western Sahel drier (− 13.5%). Future evapotranspiration is reduced across most of West Africa due to the CO2 fertilisation effect causing lower transpiration. Potential groundwater recharge (soil drainage at the bottom of a 3 m deep soil column), is predicted to increase from 0% to 16% of rainfall under present climate, to 1–20% in the future, doubling from ~ 5% to ~ 10% in northern Ghana and the eastern Sahel. Potential recharge increases largely due to increased soil hydraulic conductivity, caused by higher soil moisture resulting from increased rainfall and reduced transpiration. Other factors have only a minor influence on the water balance and potential recharge, including rainfall intensity and land use type. A predicted increase in future potential groundwater recharge is significant as development of groundwater resources is seen as a key means to meet growing water demand in West Africa.